Ameliorative effects of quercetin against bisphenol A-caused oxidative stress in human erythrocytes: an in vitro and in silico study. Issue 6 (13th September 2018) - Sangai, Neha P.; Patel, Chirag N.; Pandya, Himanshu A.
Graphical Abstract: Abstract: Bisphenol A (BPA) is an endocrine disruptor of xenobiotic type, mainly used for the production of polycarbonate plastic, epoxy resins and non-polymer additives. Because of its wide usages in the environment, the toxic effects of BPA have proved to be harmful to human health. However, its effects on human haemoglobin remain unclear. The affinity between BPA and haemoglobin, as well as erythrocytes, is an important factor in understanding the mechanism of the toxicity of BPA. Flavonoids are strong antioxidants that prevent oxidative stress and Quercetin is a flavonoid found in numerous vegetables and fruits. Therefore, the present investigation was undertaken to investigate whether Quercetin can be used to alleviate the toxic effects of BPA in vitro in human red blood cells (RBC). Venous blood samples were collected from healthy, well-nourished adult volunteers (25–30 years old) by phlebotomy. In a RBC suspension with a cell density of 2 × 104 cell per mL, the concentration of BPA (25–150 µg mL −1 ) was found to cause an increase in the lipid peroxidation (LPO) and a decrease in the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) in human RBC. However, the concurrent addition of BPA (150 µg mL −1 ) and quercetin (10–50 µg mL −1 ) lead to significant amelioration. In silico studies gave structural insight into BPA and quercetin to decipher the plausible binding mechanism and molecular level recognition.